Growth and LC-PUFA production of the cold-adapted microalga Koliella antarctica in photobioreactors - Suzuki, Hirono; Hulatt, Christopher Jonathan; Wijffels, Rene Hubertus; Kiron, Viswanath (Journal of Applied Phycology, 2018)
publishedVersion Paid Open Access